Policy Capacity and Governance Challenges in Indonesia’s MBG (Free Nutritious Meal) Program - Andi Masrich; Sarwani; Heru Rochmansjah (International Journal of Science and Society, 2026)
Indonesia’s MBG (Free Nutritious Meal) Program has emerged as a strategic national policy aimed at improving nutritional quality, reducing stunting prevalence, and strengthening human resource development through food-based social intervention. Despite its ambitious objectives, the implementation of the MBG Program continues to face various governance and policy capacity challenges across multiple administrative levels. This study aims to analyze the dimensions of policy capacity and governance challenges in the implementation of Indonesia’s MBG Program using a literature review approach. The study employs a qualitative literature review method by examining academic articles, government reports, policy documents, and previous studies related to public policy, policy capacity, nutrition governance, and food security programs. The analytical framework is based on the policy capacity model encompassing analytical, operational, and political capacities within public sector governance. The findings indicate that analytical capacity challenges are reflected in limited evidence-based policy formulation, weak data integration, and inadequate policy evaluation mechanisms. Operational capacity problems are associated with institutional readiness, logistical distribution, infrastructure limitations, and food safety management. In addition, political capacity challenges include policy coordination issues, stakeholder engagement gaps, budget sustainability concerns, and inconsistencies in governance support between central and local governments. The study further reveals that governance complexity significantly influences the effectiveness and sustainability of the MBG Program implementation in Indonesia. This article contributes to the literature on public policy and governance by providing a comprehensive analysis of policy capacity dimensions in large-scale nutrition intervention programs within developing countries. The study also offers strategic policy recommendations for strengthening institutional coordination, governance effectiveness, and sustainable policy implementation in Indonesia’s MBG Program.